Pengaruh Komitmen Terhadap Kinerja Pegawai Pada Kantor Kecamatan Kotabaru Jambi - Balya Haji Ahmar (Science of Management and Students Research Journal (SMS), 2019)
Employee performance improvement will bring progress for the company, therefore efforts to enhance employee performance. The purpose of this research is to know the commitment on performance at Kantor Kecamatan Kotabaru Jambi and to find out how the influence or commitment on performance at Kantor Kecamatan Kotabaru Jambi.            This research is a desciptive quantitative research and analysis tool used in this research are simple linear regression is useful to see the direction of the relationship between the variable bound against free. For the purpose of answering the purpose number 2 used statistical test t. The correlation coefficient to know how the relationship between variables and coefficients of determination of useful to see the magnitude of the influence of the variable bound against free.            Kantor Kecamatan Kotabaru Jambi is a functional unit that functions as a center for community service work as well as the role of foresting relic society working relic in order to improve the ability of the hifup welfare and provide maxiun service thoroughly and integrated to society.       The calculation SPSS Y = 14.066 + 0.428 X + e of the equations looks positive influence between commitment (X) on performance (Y) at Kantor Kecamatan Kotabaru Jambi. From the result of the obtained values SPSS (coefficient) r2 this figure amounted 36,3% states that the variable commitment (X) is able to explain the variabel performence (Y) is 36,3% and the remaining 63,7% is explained by other factors which is not included in the research model. Partially the commitment have an influence on performance at Kantor Kecamatan Kotabaru Jambi.            Employees should always keep commitment to work properlu so that the goals can be achieved and the leadership should be have well and keep the work environment so that performance can be maintained.